Alternative splicing, spatiotemporal expression of TEP family genes in Yesso scallop (Patinopecten yessoensis) and their disparity in responses to ocean acidification. Issue 95 (December 2019) - Xing, Qiang; Wang, Jing; Zhao, Qiang; Liao, Huan; Xun, Xiaogang; Yang, Zujing; Huang, Xiaoting; Bao, Zhenmin
Abstract: The complement system constitutes a highly sophisticated and powerful body defense machinery acting in the innate immunity of both vertebrates and invertebrates. As central components of the complement system, significant effects of thioester-containing protein (TEP) family members on immunity have been reported in most vertebrates and in some invertebrates, but the spatiotemporal expression and regulatory patterns of TEP family genes under environmental stress have been less widely investigated in scallops. In this study, expression profiling of TEP family members in the Yesso scallop Patinopecten yessoensis (designated PyTEPs ) was performed at all developmental stages, in different healthy adult tissues, and in mantles during exposure to different levels of acidification (pH = 6.5 and 7.5) for different time points (3, 6, 12 and 24 h); this profiling was accomplished through in silico analysis of transcriptome and genome databases. Spatiotemporal expression patterns revealed that PyTEPs had specific functional differentiation in all stages of growth and development of the scallop. Expression analysis confirmed the inducible expression patterns of PyTEPs during exposure to acidification. Gene duplication and alternative splicing events simultaneously occurred in PyTEP1 . Seven different cDNA variants of PyTEP1 (designated PyTEP1-A–PyTEP1-G) were identified in the scallop mantle transcriptome during acidic stress. These variants were produced by the alternative splicing of seven differentially transcribed exons (exons 18–24), which encode the highly variable central region. The responses to immune stress may have arisen through the gene duplication and alternative splicing of PyTEP1 . The sequence diversity of PyTEP1 isoforms and their different expression profiles in response to ocean acidification (OA) suggested a mechanism used by scallops to differentiate and regulate PyTEP1 gene expression. Collectively, these results demonstrate the gene duplication and alternative splicing of TEP family genes and provide valuable resources for elucidating their versatile roles in bivalve innate immune responses to OA challenge. Highlights: Seven PyTEP1 splices were identified in Yesso scallop transcriptome. Gene duplication and alternative splicing simultaneously occurred in PyTEP1. Spatiotemporal expressions revealed PyTEPs had functional differentiations. The five PyTEPs showed diverse immune response patterns to OA. Functional differentiations of PyTEP1 splices have been arisen to immune stress.